Examination of the behaviour of young rabbits kept on deep litter at the different stages of rearing - Jekkel, Gabriella; Milisits, Gábor; Biróné Németh, Edit (Animal welfare, Ethology and Housing Systems (AWETH), 2008)
The objective of the present study was to analyse some behaviour forms of rabbits kept on wire net floor for the whole fattening period and that of rabbits placed to deep litter at various ages using different stocking densities. Based on the type of floor four experimental groups were created: 1. rabbits were reared on wire net floor from 5 to 11 weeks of age; 2. wire net floor was changed to deep litter at 7 weeks of age; 3. wire net floor was changed to deep litter at 9 weeks of age; 4. rabbits were reared on deep litter from 5 to 11 weeks of age. In each group three different stocking densities (8, 12 and 16 rabbits/m²) were used. About the rabbits 24-hours video recordings were made every week on the same day. The actual behavioural form of each rabbit was recorded in every 10 minutes. Based on the results, it was established that changing the floor type from wire net to deep litter significantly decreased the eating frequency. The drinking frequency was not affected by placing bedding material into the pens. The frequency of moving was not significantly affected neither by the type of floor nor by the stocking density. In spite of this, the type of floor, the stocking density and also the age of the rabbits had a significant effect on the frequency of the resting and comfort behaviour. Aggressive animals were observed only in a very few number during the experimental period. The stereotype behavioural form was detected mainly in the first two week of the experiment and decreased thereafter. The frequency of straw eating decreased with increasing the time from changing the type of floor. Based on the results it was concluded, that rabbits are eating the straw after placing it on the wire net floor and, therefore their feed consumption decreases. Keeping rabbits on deep litter at low stocking density – as required in the point of animal welfare’s view – results in a decrease in the frequency of resting and comfort behaviour and has no effect on the frequency of other behavioural forms.
Keywords: rabbit; ethology; behaviour; floor; deep litter